L’intégration du l’énergie photovoltaïque pour l’étude de bilan énergétique - Zouzou, Nouamane; Ghendir, Mabrouk-Abdallah; Chennouf, Chokri (université d'eloued, 2023)
"The objective of this thesis is to study the performance of the photovoltaic system connected to the network and the energy balance in the residential building in the Algerian desert, province of El Oued, as a model. It is a model for optimizing the size of photovoltaic systems connected to the grid. The current model was implemented in MATLAB Simulink, the prevailing weather conditions, the peak power of a photovoltaic generator and the presence and absence of a power grid. Our contribution provided the triple benefit of a system without electrochemical storage, cost reduction and increased reliability of the grid-connected photovoltaic system." "الهدف من هذه الرسالة هو دراسة أداء النظام الكهروضوئي المتصل بالشبكة وتوازن الطاقة في المبنى السكني في صحراء الجزائر والية الوادي نموذجا. وهو نموذج لتحسين حجم النظم الكهروضوئية المتصلة بالشبكة. تم تنفيذ النموذج الحالي في ماتالب سيملينك، والظروف الجوية السائدة، وقوة الذروة لمولد كهروضوئي، ووجود وغياب شبكة الكهرباء. قدمت مساهمتنا ميزة ثالثية، نظام بدون تخزين كهروكيميائية وخفض التكلفة وزيادة موثوقية النظام الكهروضوئي المتصل بالشبكة الكهرباء."
des thèses commande Electriqueمذكرات ماستر تخصص تحكم كهربائي
Keywords: grid-connected photovoltaic; Energy performance Energy balance Bioclimatic housing.; "الكهروضوئية؛ الكهروضوئية المتصلة بالشبكة؛ أداء الطاقة؛ توازن الطاقة؛ السكن البيو مناخي."